A Comparative Study of the Effects of Cumin and Mefenamic Acid Capsules on Menstrual Bleeding in IUD Users: A Randomized Triple Blind Clinical Trial - NM Rajabi; M Modarres; GH Amin; N Bahrani (Journal of Medicinal Plants, 2015)
Background: Unusual menstrual bleeding is one of the most common side effects of IUD. Objective: Considering public enthusiasm to the use of herbal medicine, this study conducted to compare the effects of cumin and mefenamic acid capsules on menstrual bleeding in IUD users. Methods: This crossover triple-blind randomized clnical trial study was performed on 100 IUD users who came to 6 health centers in Karaj. Research took place in three stages. In the first stage menstrual bleeding was measured by using Hygam table. In the second stage all participants were randomly allocated to mefenamic acid and cumin groups. They took capsules for two consecutive cycle. In the third stage each research unit received the same treatment of the opposite group with replacing the medicine for two more consecutive cycle. Menstrual bleeding was assessed by using Hygam table for 5 cycle. Considering that the maximum efficacy time for cumin was 24 hours and for Mefenamic acid was6 to 8 hours, the use of drugs in 7 days during menstruation, had no effect on subsequent cycles. Data, was analyse by Chi-square and Fisherchr('39')s exact test, paired t-test, Wilcoxon. Results: The mean of menstrual bleeding was 154.26±60.08 and after treatment was 106.68±45.38 and 105.8±40.56 in the mefenamic acid and cumin groups. There was a significant difference in decrease of pain intensity in both groups (p<0.001). There wasn’t a significant difference in decrease of pain intensity between two groups. Conclusion: This study showed that cumin same as mefenamic acid capsules can decrease menstrual bleeding effectively. Therefore it is recommended to use it in the treatment of menstrual bleeding in IUD users.